2006
DOI: 10.1073/pnas.0600499103
|View full text |Cite
|
Sign up to set email alerts
|

Kupffer cell-dependent TNF-α signaling mediates injury in the arterialized small-for-size liver transplantation in the mouse

Abstract: Implantation of small liver grafts causes liver injury and defective regeneration leading to graft failure. We investigated whether Kupffer cell-dependent TNF-␣ signaling contributes to this poor outcome. Partial 30% liver transplantation was performed in C57BL͞6 wild-type mice (control group), and in three groups with down-regulation of the TNF-␣ pathway: (i) TNF receptor 1 knockout [TNFR-1(؊͞؊)] mice, and mice pretreated with (ii) gadolinium chloride or (iii) pentoxifylline (PTX). Fifty-percent partial liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
68
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 44 publications
3
68
0
Order By: Relevance
“…After resection the remaining liver can regenerate to a fully functional organ [1][2][3] . Tissue damage due to the surgical process further decreases the amount of healthy remnant liver tissue leading to an additional reduction in functional liver capacity in the postoperative period [4,5] . This situation can lead to liver insufficiency and, ultimately, to liver failure and death [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After resection the remaining liver can regenerate to a fully functional organ [1][2][3] . Tissue damage due to the surgical process further decreases the amount of healthy remnant liver tissue leading to an additional reduction in functional liver capacity in the postoperative period [4,5] . This situation can lead to liver insufficiency and, ultimately, to liver failure and death [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the role of proregenerative cytokines (e.g. IL-6 and TNF-a) and the role of transcription factors such as NF-κB are ambiguous [5,[20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that PTX administration increases the production of anti-inflammatory and growth promoting factors (IL-6 and IL-10) in a small-for-size liver transplantation in mice [13] . It was concluded that these effects were related to inhibition of the TNF-α signaling pathway [13] .…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that PTX administration increases the production of anti-inflammatory and growth promoting factors (IL-6 and IL-10) in a small-for-size liver transplantation in mice [13] . It was concluded that these effects were related to inhibition of the TNF-α signaling pathway [13] . However, in the present study we did not find a reduction in TNF-α levels in liver tissue following the administration of PTX, suggesting that the production of TNF-α in the liver tissue follows a different signaling pathway from that of macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation